Tesserae: essaying fragments of a life - Robertson, Rachel (2019)
‘Tesserae’ enacts its own content, being a lyric essay about memory, brokenness and how lyric essays can both tell a partial story and open up questions about this story. The mosaic is metaphor and subject, as the narrator remembers moments from her childhood and intimates their effects on her later life, and on her writing. The work aims to demonstrate how the lyric essay form can support life writing that embraces narratorial subjectivity that is complex, fluid, contingent and relational whilst still adhering to Lejeune’s (1989) ‘autobiographical pact’.